Identification of The Use of Substances Among Orthodontic Patients - Jia, Lim Yan; Yi, Tan Jia; Yahya, Nurul Asyikin; Abdullah, Asma Alhusna Abang (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective: Substance abuse among the youth is rising and may cause abnormal manifestation in the oral cavity. Hence, the orthodontic dental setting is a potential venue to detect substance abuse among these young patients. This study aimed at identifying the use of substances among young adults attending orthodontic clinics and describing their oral manifestations related to the substances. Methods: A cross-sectional study was conducted between the periods of October 2020 to January 2021. Identification of substance abuse was done to 138 orthodontic patients aged 15 to 30 years old using an online validated questionnaire. The validated questionnaire included the patient's demographic data and their use of substances i.e. tobacco, vape and alcohol. 47 subjects were clinically assessed for intraoral manifestations of substance use. Ethical approval and consent from all subjects were sought prior to the start of the recruitment. Results: The prevalence of subjects who smoke was 2.9%. A total of 4.35% and 15.22% of the respondents were identified as vape users and alcohol users, respectively. However, none of the respondents were abusers or dependents based on the frequency and duration of the usage. For the clinical examination, nicotine stomatitis was detected in one subject (2.13%). Periodontal status with BPE ≥ 3 was identified in 24 subjects (51.06%). Tooth staining was detected on 5 subjects (11.90%) and dental erosion was identified in one subject (2.13%). Dental attrition was found on 15 subjects (31.91%). Conclusion: A minority of young adults attending an orthodontic clinic are light users of either cigarettes, vapes or alcohol. Intraoral manifestations of substance usage were also minimal. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S29